Association between non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and cardiovascular disease mortality in patients with type 2 diabetes mellitus and diabetic kidney disease - Li, Zhiyu; Xu, Hongyang (Frontiers in Endocrinology, 2025)
PurposeNon-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) represents an essential lipid index and is closely related to the occurrence and development of diabetes and cardiovascular diseases (CVDs). Therefore, this study is intended to further investigate the association between the NHHR index and the mortality rate of CVDs in patients with type 2 diabetes mellitus (T2DM) and diabetic kidney disease (DKD).MethodsThe research sample was selected from the NHANES (National Health and Nutrition Examination Survey) database, and 5136 individuals were categorized based on quartiles of the NHHR index. Restricted cubic plots and COX regression models were utilized to examine the thresholds and patterns of the NHHR index in relation to the risk of CVDs mortality among T2DM patients as well as those with DKD. Subgroup analyses and p-values were used to evaluate interactions between different variables.ResultsThe NHHR index shows a nonlinear association with cardiovascular mortality in two patient groups, following an L-shaped pattern. In individuals with T2DM, a lower NHHR index (<1.68) correlates with an increased risk of death, demonstrating a 72.8% reduction in mortality risk for each unit increase in NHHR below this threshold. Similarly, among patients with DKD, a lower NHHR index (<1.82) is associated with heightened cardiovascular mortality risk, indicating a 48.2% reduction in death risk for each unit increase in NHHR beneath the specified threshold. In patients diagnosed with T2DM, the third quartile of the NHHR index was significantly linked to reduced mortality risk; the association remained consistent even when additional variables were considered [Hazard Ratio (HR), 0.82; 95% Confidence Interval (CI) (0.69-0.97); P=0.019]. Among patients with DKD, cardiovascular mortality was notably higher in the third and fourth quartiles of the NHHR index [Quartile3 HR, 1.57; 95% CI (1.10-2.24), P=0.013; Quartile4 HR, 2.04; 95% CI (1.28-3.26), P=0.003].ConclusionsThe NHHR is below 1.68, and an increase in the NHHR index is associated with a reduced risk of CVD mortality in patients with T2DM. Similarly, when the NHHR falls below 1.82, an elevation in the NHHR index correlates with a decreased risk of CVD mortality in patients with DKD.